Leadership in Action : Inklings - Fathers, Sons, and Mutual Respect - Campbell, David (Center for Creative Leadership, 2005)
A son who in his own mind never matches his father's performance is vulnerable to a life that feels incomplete, unfulfilled, and unsatisfying.